Aprovechamiento del aceite doméstico residual (ADR) para la generación de biodiesel en Iquitos, Loreto, 2019 - Del Aguila Ojanama, Wagner Michelle (2022)
The project was carried out in the laboratory of organic chemistry of the Faculty of Chemical Engineering of the National University of the Peruvian Amazon, aiming to obtain biodiesel from residual domestic oil. The oil was collected from a total of 384 houses in the city of Iquitos, which was pre-treated to remove solids and moisture; to the properly treated oil some quality tests were performed, being the determination of acidity index the most important, because of that result the amount of catalyst to be used in the reaction was determined, this being 0,4173 gr NaOH per 100 ml of residual domestic oil. Subsequently, a reaction process called transesterification was performed, using 100 ml of residual domestic oil with different reaction temperatures (room temperature, 45°C and 65°C) and different volumes of methanol (20 ml, 40 ml and 60 ml), obtaining different yields of the nine combinations evaluated; of these results and performing Tukey's significance test, it was determined that the optimum temperature and volume of methanol needed to obtain higher biodiesel yield is the combination of 45°C with a with a volume between 40 and 60 ml of methanol. Finally, in order to conclude that the residual domestic oil generated in the city of Iquitos meets the necessary characteristics to be used through its transformation into biodiesel, quality tests were carried out, which showed that biodiesel has properties within national and international parameters.